Enhanced thermoelectric efficiency in armchair silicene nanoribbons decorated by Mn. (March 2023) - Sirohi, Ankit; Singh, Jawar
Abstract: In this study, we use density functional theory to investigate the structural stability as well as the magnetic and thermoelectric properties of Mn-passivated armchair silicene nanoribbons (Mn-ASiNRs). All structures considered in this study were thermodynamically stable, and existed in ferromagnetic ground states with a Curie temperature greater than 400 K. The Mn-ASiNRs showed spin-polarized electronic properties that were tunable with respect to their width (N). Mn-ASiNRs with N = 4, 5, and 7 (4-, 5- and 7-Mn-ASiNRs) were semiconducting, while 6-Mn-ASiNR was half-metallic and 8-Mn-ASiNR was metallic. We simulated N-Mn-ASiNR-based devices to evaluate their thermoelectric properties, and observed a high-spin Seebeck coefficient (S S ) of 1800 μ V/K at μ = 0 and a charge Seebeck coefficient (S C ) of 1350 μ V/K at μ = − 0 . 17 eV for 4-Mn-ASiNRs. We obtained significantly enhanced charge and spin thermoelectric figures of merit (Z C T and Z S T) compared with those of pristine nanoribbons (H-ASiNRs) that had maximum values of 25 and 18 at room temperature for 4- and 7-Mn-ASiNRs, respectively. Z C T and Z S T further improved to values of 150 and 190, respectively, at temperatures lower than 100 K owing to a rapid increase in S C and S S, and exhibited decreased thermal conductance (K t ). Moreover, we showed that a thermally driven spin current with a negligibly small charge current can be generated by our devices. The results of this theoretical study indicate that Mn-ASiNR can be used to develop effective thermoelectric energy conversion devices.